Directive Speech Acts in Teacher-Student Interaction and Implicit Meanings in Social Media Discourse: A Pragmatic and Discourse Study - Rimang, Sitti Suwadah; Sartika, Dewi; Anas, Anas; Rahayu, Andi Sri (Edumaspul: Jurnal Pendidikan, 2025)
This study examines the phenomenon of directive speech acts in two distinct contexts: face-to-face interaction between teachers and students in senior high schools (SMA), and implicit communication practices on social media. Directive speech acts play a significant role in constructing power relations, delivering commands, requests, and even sarcasm. This research employs a descriptive qualitative method using discourse analysis, complemented by quantitative data from case studies. Data were collected from classroom transcripts and social media posts, analyzed through the lens of speech act theory Austin & Searle, implicature Grice, and critical discourse analysis Fairclough. Case studies were conducted at two senior high schools in South Sulawesi, with secondary data obtained from digital communication journals. The findings show that 62% of teacher directives were explicit, while 73% of directives on social media were implicit, expressed through sarcasm or metaphors. This article highlights the importance of social context, power relations, and pragmatic intentions in shaping the structure and strategy of directive delivery.